Sermin Prazgodovinska in zgodnjerimska naselbina v severozahodni Istri = A prehistoric and Early Roman settlement in Northwestern Istria - Horvat, Jana (Opera Instituti Archaeologici Sloveniae, 1997)
The following results from excavations carried out in 1987 at Sermin near Koper are presented in the monograph: the extent of the settlement, the stratigraphy, the remains of Bronze Age houses and Roman levelling of the ground. Metal, glass and bone material finds, as well as Prehistoric and Roman pottery, are analyzed in detail. It was determined that settlement was of long duration, probably continuous from the Middle Neolithic to the middle of the 1st century AD. Due tot ehir abundance, material finds dating to the Middle and Late Bronze Ages as well as the Early Roman period are more striking. The settlement at Sermin was constantly situated in the middle of trade and cultural currents between Italy, the Balkans and the Mediterranean region. The material finds are also an indication of the significance of the settlement during the period of the earliest Romanization. Attesting the plentiful production of wine and amphorae along the Adriatic coast of Italy already from the middle of the 2nd centruy BC, the archaeological chapters are complemented by chemical and mineralogical research on the ceramics of the amphorae. The paleo-vegetational conditions in the coastal region of Koper are presented at the end. The development of settlement in the region of northwestern Istria from Prehistoric times to the Early Middle Ages is described in the supplement.